Bi-nucleation of podocytes is uniformly accompanied by foot processes widening in renal disease - Muehldorfer, Johanna; Pfister, Eva; Buettner-Herold, Maike; Klewer, Monika; Amann, Kerstin Ute; Daniel, Christoph (Nephrology Dialysis Transplantation, 2017)
Podocytes are terminally differentiated glomerular cells expressing a highly complex architecture and lacking the ability to proliferate. However, during renal injury or stress these cells can re-enter into the cell cycle but fail to divide. As a consequence, bi- and multi-nucleated podocytes can be identified in renal biopsies from patients with various kidney diseases. It is still unclear whether the occurrence of such cells is dependent on or correlates with renal damage and if bi- or multi-nucleation results in ultrastructural alterations such as e.g. foot process effacement. Therefore, we investigated the frequency, correlation with clinical parameters and morphological consequences of podocyte bi- or multi-nucleation in a cohort of 377 patients suffering from different renal diseases.Renal biopsies from patients with minimal change disease (MCD; n = 93), IgA-glomerulonephritis (IgA-GN, n = 95), lupus nephritis (LN; n = 90) and diabetic nephropathy (DN; n = 99) were investigated for the occurrence of bi-nucleated or multi-nucleated podocytes using semi-thin sections and light-microscopy at 1000× magnification. The frequency of bi-nucleation and multi-nucleation in podocytes was correlated with clinical parameters and markers of renal injury. In addition, ultrastructural morphological features associated with podocyte bi- or multi-nucleation were analysed by scanning transmission electron microscopy at various magnifications.Ultrastructural analysis of podocyte nuclear morphology revealed a broad spectrum of nuclear appearances. Therefore, podocytes were classified in cells with mono-nucleated, lobulated, potential bi-nucleated, symmetrically bi-nucleated, asymmetrically bi-nucleated and multi-nucleated nuclear morphology. In 65-80% of all investigated glomeruli only mono-nuclear podocytes were identified. The highest frequency of bi-nucleated podocytes was found in patients with IgA-GN (18.6%) and the lowest in patients with DN (5.6%). The proportion of bi-nucleated podocytes with asymmetric nuclear morphology was about 50% of all bi-nucleated podocytes and independent of the underlying renal disease. In addition, ultrastructural analysis by electron microscopy showed significant widening of foot processes in bi-nucleated compared with mono-nucleated podocytes. Interestingly, foot process width of podocytes with lobulated nuclei was also significantly increased compared with podocytes with normal mono-nuclear morphology. Furthermore, podocyte density per glomerular area was significantly lower in glomeruli with bi-nucleated podocytes. Due to the relatively low frequency of bi- and multi-nucleated podocytes, correlations with clinical parameters were weak and dependent on renal disease.The frequency of bi-nucleated podocytes was highest in IgA-GN but can also be observed in all investigated renal diseases. In podocytes with altered nuclear morphology particularly in bi- and multi-nucleated podocytes ultrastructural analysis of podocytes revealed significant widening of foot processes as a potential maladaptive structural consequence.
EVALuna2:25559